2016
DOI: 10.1111/trf.13693
|View full text |Cite
|
Sign up to set email alerts
|

Leukoreduced red blood cell transfusions do not induce platelet glycoprotein antibodies in patients with sickle cell disease

Abstract: Leukocyte-reduced RBC transfusions do not appear to induce platelet-specific glycoprotein antibodies. The positive platelet-specific glycoprotein antibody results from this study may represent platelet autoantibodies, platelet alloantibodies, or false-positive reactions. A better understanding of the immunobiology of patients with SCD at baseline and after blood product exposure may help improve future transfusion and transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Additional variables, including patient age, transplant donor/recipient ABO matching, conditioning regimen, and the incidence of acute GVHD, were also evaluated. As previous work has suggested that RBC transfusions do not appear to cause human platelet antigen (HPA) antibodies (Nickel et al , ), HPA alloimmunization was not studied.…”
mentioning
confidence: 99%
“…Additional variables, including patient age, transplant donor/recipient ABO matching, conditioning regimen, and the incidence of acute GVHD, were also evaluated. As previous work has suggested that RBC transfusions do not appear to cause human platelet antigen (HPA) antibodies (Nickel et al , ), HPA alloimmunization was not studied.…”
mentioning
confidence: 99%